(untitled) - Barber, Tiki; 1975-; Barber, Ronde; 1975-; Burleigh, Robert; Root, Barry (New York, N.Y., 2004)
Introduces twin brothers Tiki and Ronde Barber, who worked hard to overcome obstacles and became National Football League stars, one as runningback for the New York Giants, the other as cornerback for the Tampa Bay Bucs.
"A Paula Wiseman book."
Accelerated Reader AR
Keywords: Barber, Tiki; 1975-; Juvenile literature; Barber, Ronde; 1975-; Juvenile literature; United States; Biography; Brothers; Biography; Football players; United States